NMR workflow from data processing to metabolite identification - Le Gall, Gwénaëlle (Henry Stewart Talks, 2017)
Historic and description of NMR metabolomics, Samples and principle of NMR, Equipment and recording of NMR spectra, Data processing and data analysis, Metabolite identification, Metabolite profiling of obese mice: case study
Reviewed at 2023/07/11